Implementasi Algoritma k-Nearest Neighbor (k-NN) dalam Klasifikasi Status Gizi Balita - Sahara Syarifatul Choeriyah; Riezan Syauqi Fanhas; Adittia Fathah; Haerul Pebriyansyah (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Toddlers are children under the age of 5 years or 0-60 months. This age is included in a group that is at high risk of disease. Nutritional status in toddlers is an important factor that must be considered because the development of toddlers is very important for their bodies which are still very vulnerable to the name malnutrition.The purpose of this study is to group the nutritional status of toddlers by utilizing the k-NN algorithm and knowing the level of accuracy. The method used in this research is quantitative using the k-NN algorithm. While the evaluation uses Confusion Matrix The results showed an AUC value of 85.1%. Based on these results, it can be concluded that the k-NN algorithm is well used for the classification of toddler nutrition in the future.